Implementing Mudharabah and Musharakah Contracts in the Eid Savings Scheme at BMT Al-Yaman Banyuwangi - Elfa Miftahul Jannah; Mira Ustanti (ICO EDUSHA, 2025)
This study aims to analyze the implementation mechanism and sharia compliance of the mudharabah musyarakah contract in the Simpanan Hari Raya (Holiday Savings) product at BMT Al-Yaman Banyuwangi. Using a descriptive qualitative approach, data were collected through interviews, observation, and document analysis. The results indicate that the product employs a combined mudharabah musyarakah scheme, with members as capital owners (shahibul maal) and the BMT as both manager (mudharib) and capital participant. The implementation mechanism encompasses member registration, contract explanation, profit-sharing ratio determination, routine deposits, and fund management within a halal, low-risk financing portfolio. Profit distribution occurs before religious holidays in cash or in-kind. The contract application adheres to sharia principles, including transparency, clear profit-sharing, no upfront fixed profit guarantee, and the use of funds for halal activities. The study concludes that while sharia principles are met, enhancing member education and strengthening risk management are crucial for the contract's sustainability. These findings support prior research on the effectiveness of mudharabah musyarakah in Islamic microfinance savings products. Keywords : mudharabah musyarakah, holiday savings, BMT, profit sharing.